Modeling of Wake Effects in Steady State Mixing Plane Simulations of a High Lift Turbine Cascade with Different Combinations of Wake Passing Frequency and Wake Orientation - Alexander Führing; Dragan Kozulovic; Christoph Bode; Matthias Franke (International Symposium on Transport Phenomena and Dynamics of Rotating Machinery 2020, 2020)
Due to operation at low Reynolds numbers, low pressure turbines of aircraft engines mostly show large laminar boundary layers and transitional separation bubbles which considerably change their viscous losses when interacting with impinging wakes. The change of loss depends on several wake parameters, among others on wake passing frequency and wake orientation. In the present work, these parameters are expressed in terms of Strouhal number and flow coefficient and their influence is investigated by means of unsteady Reynolds-averaged Navier-Stokes (RANS) simulations. Different combinations of both wake parameters which are typical of aircraft engine conditions, are prescribed upstream of a high lift turbine cascade, while the Reynolds number and Mach number are kept constant. The solver TRACE by DLR and MTU Aero Engines together with the gamma-Re_theta transition model by Langtry and Menter has been used. Further, the wake profile is representative for upstream turbine profiles and is prescribed by a correlation framework which has been calibrated in previous work. A newly developed quasi-unsteady wake model (QUWM) is applied in order to model the effects of periodically passing wakes in steady state simulations involving mixing plane interfaces. It is shown that the gap between unsteady and steady state simulations is narrowed significantly by the QUWM while still maintaining quick turnaround times that are crucial in industrial flow solver applications.